0564 Effects of Phrenic Nerve Stimulation on Sleep Architecture and Quality of Life Through 12 Months. (27th April 2018) - Boero, J; Khayat, R; Graff, J; Javaheri, S; Costanzo, M
Abstract: Introduction: We have previously reported that the rem: edē System is a safe and effective implantable device providing transvenous phrenic nerve stimulation for the treatment of central sleep apnea (CSA). Here, we report the impact of long-term therapy of CSA on sleep architecture and quality of life (QoL). Methods: rem: edē System Pivotal Trial patients randomized to therapy (n = 73) were followed through 12 months (M) to assess continued benefit on CSA, sleep architecture and QoL. Patients with polysomnograms at baseline, 6 and 12M were analyzed (n=56). Results are presented as mean ± standard deviation (nominal 2-sided p-value). All polysomnograms were scored centrally by individuals unaware of patients characteristics. Results: Central apnea index decreased from 32 ± 19 events/hour to 6 ± 9 at 6M (p<.001) and 4 ± 7 at 12M (p<.001). Apnea hypopnea index (AHI) improved from 50 ± 19 to 27 ± 20 (p<.001) and 23 ± 22 (p<.001) events/hour at 6 and 12M, respectively. In concert with improvement in sleep disordered breathing, respiratory arousal index decreased from 39 ± 19 events/hour to 18 ± 15 (p<.001) and 16 ± 14 (p<.001) at 6 and 12M, while spontaneous arousals remained unchanged [7 ± 7 events/hour at baseline, 8 ± 8 at 6M (p=.44) and 8 ± 8 at 12M (p=.24)]. N1 decreased from 33 ± 19% of total sleep time to 29 ± 17% at 6 month (p=.11) and 30 ± 17% at 12M (p=.22); N2 increased from 50 ± 15% to 53 ± 14% (p=0.09) and 52 ± 15% (p=.19); N3 decreased from 6 ± 9% to 5 ± 7% (p=.42) and 4 ± 6%(p=.13); % time in REM sleep increased from 11 ± 7% to 13 ± 9% (p=0.20) and 14 ± 9% (p=.05). QoL improvements were observed by a reduction in Epworth Sleepiness Scale from 11 ± 5 to 7 ± 4 (p<.001) and 7 ± 3 (p<.001) at 6 and 12M, and 61% of subjects responded markedly/moderately improved on the Patient Global Assessment at each time point. Conclusion: Phrenic nerve stimulation therapy produces improvements in CSA and sleep architecture concordant with improved QoL that is sustained through 12 months. Support (If Any): This study was sponsored by Respicardia, Inc. (Minnetonka, MN).